RETRACTED:Developing Project Based Learning E-Module for the Course of Video Editing - Ketut Krisnayuni; I Gede Mahendra Darmawiguna; I Made Putrama (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “Developing Project Based Learning E-Module for the Course of Video Editing”, Vol 23, No 3, pp. 265-272, May 2017DOI: http://dx.doi.org/10.21831/jptk.v23i3.13389This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika (KARMAPATI) ISSN: 2252-9063, Vol. 4, No. 5, 2015The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.